Data Governance: Enhancing Innovation and Protecting Against Its Risks - Max Grafenstein; Alina Wernick; Christopher Olk (Intereconomics, 2019)
Big Data is expected to unleash data-driven innovation,which is supposed to better address and solve challengesin our society. As a so-called non-rival good, the sharingand re-using of data by one actor does not diminish its valuefor other actors and can create significant spillover effects. Data is still often stored in data silos. Releasing data fromsilos and sharing it may enhance social and economic welfare.
Keywords: 330